Cyclic compounds incorporating two or four alkyne units in close proximity - theory and experiments - Gleiter, Rolf; Haberhauer, Gebhard (European journal of organic chemistry, 2018)
In the first part we summarize the results of experiments performed with medium-sized cyclic compounds (10, 12, 14 ring size) incorporating either two opposite acetylene units or two buta-1,3-diyne units. The acetylene units in the 10-membered rings react either thermally or with the aid of AuI catalysis to afford bicyclo[4.4.0]-1,6-diene rings. Reduction with H2/Pd or addition of I2 to 12-membered rings containing two opposite buta-1,3-diyne units yield 5?6?5 cycles, whereas 14-membered rings react with HCl to afford 5?8?5 or 6?6?6 rings. In the second part we discuss the results of calculations relating to 1,6-transannular ring closure of cyclodeca-1,6-diyne derivatives in which the two triple bonds are each flanked either with two oxygen atoms or with two NH groups. For the resulting heterocycles, dicarbenes with singlet ground states are predicted. The extension of these model calculations led us to look at substituted phenylacetylenes (e.g., Ph?C≡C?OMe) for which dimerization to cyclobutadiene derivatives was predicted. This forecast could be verified by trapping the cyclobutadiene products with maleic acid.
Gesehen am 03.05.2019